2016
DOI: 10.1136/bjophthalmol-2016-308827
|View full text |Cite
|
Sign up to set email alerts
|

S100A8 and S100A9 proteins are expressed by human corneal stromal dendritic cells

Abstract: A8 and A9 expression may distinguish between subpopulations of DC that reside in different regions of the human cornea and may influence their maturation status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In contrast, S100A8/A9 also have anti-in ammatory functions in various microenvironments. S100A8/A9 inhibit the differentiation and functioning of dendritic cells (30), induce myeloid-derived suppressor cells (31), and increase the functions of regulatory T-lymphocytes (32). In our study, we found a correlation between elevated levels of S100A8/A9 and decreased survival rates in patients suffering from IPF.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast, S100A8/A9 also have anti-in ammatory functions in various microenvironments. S100A8/A9 inhibit the differentiation and functioning of dendritic cells (30), induce myeloid-derived suppressor cells (31), and increase the functions of regulatory T-lymphocytes (32). In our study, we found a correlation between elevated levels of S100A8/A9 and decreased survival rates in patients suffering from IPF.…”
Section: Discussionsupporting
confidence: 58%
“…These cells were positive for CD45, HLA-DR, and CD11c, which are characteristic markers of DCs. Thus, expression of A8 and A9 may help to distinguish between subpopulations of DCs which are present in different regions of the cornea and may impact on their maturation state [ 117 ].…”
Section: Effects Of Uv Irradiation To the Limbal Niche: Pterygium mentioning
confidence: 99%
“…Constitutive expression of S100A7 has been reported in cornea, conjunctiva, nasolacrimal ducts, and lacrimal glands. S100A8 and S100A9 were also found to be expressed by human corneal stromal cells ( Wilkinson et al, 2016 ). Ocular fluid also contains human neutrophil peptides (hNP-1 and -2), hBD-1, hBD-2, hBD-3, lactoferrin, lysozyme, and transferrin during normal conditions ( Silva et al, 2013 ).…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%